Earth negotiations : analyzing thirty years of environmental diplomacy - Chasek, Pamela S., 1961- (United Nations University Press, 2001)
Develops a model to enable greater understanding of the process by which international environmental agreements are negotiated. The goal is to determine what lessons can be learned from past cases of multilateral environmental negotiation in order to help both practitioners and scholars.